Wind-Thermal-Bundled Power Transmission by AC/DC System and Coordinated Control - A review - Xiao, HW; Du, WJ; Song, YT; Wang, Q; Ding, J; Chen, DZ; Wang, HF; Bu, SQ (IET Conference Proceedings, 2016)
HVDC for long-distance power transmission is of many significant technique advantages. Wind generation bundled with the support by conventional thermal generation enables the generation controllable and more suitable for being sent over to remote load centre. Hence Wind-thermal-bundled power transmission by AC/DC system and its coordinated control has become an actively pursued research subject recently. It has been practised in Chinese power transmission systems for the long-distance wind power transmission. This paper presents a review on the recent research progress in the field and development of practice in China. Firstly, the paper overviews the technical merits and difficulties of wind-thermal bundled power transmission by AC/DC systems to meet the need of large-scale wind power transmission. Secondly, a detailed description of employing HVDC technology for large-scale wind farms being integrated into power system is given in the paper. Main HVDC control strategies are reviewed, including current control, frequency control and additional damping control. Methods and effects of the control strategies are discussed. Finally, recent work on the coordinated control between the wind-thermal-bundled power resource control system and AC/DC transmission control system is reviewed. Several issues on the wind-thermal-bundled power transmission by AC/DC system, such as the capacity of the wind generation, system stability, etc., are addressed in the paper.